Pengembangan “MeLea Bionik” (Media Leaflet Bioentrepreneurship Hidroponik) untuk Memotivasi Generasi Milenial dalam menghadapi Keterbatasan Lahan di Kota Semarang - Ahmad Zubaid; Anif Rizqianti Hariz; Erna Wijayanti (Quagga : Jurnal Pendidikan dan Biologi, 2022)
Hydroponics based on bio-entrepreneurship is one of the efforts to protect environmental pollution by utilizing waste into a high use value, one of which is the use of plastic waste as a hydroponic growing medium. This study aims to develop a bioentrepreneurship-based hydroponic leaflet to increase the millennial generation's motivation towards agriculture by utilizing the development of Agricultural Science and Technology through the wick hydroponic system. The method used is five ADDIE paths, namely: Analysis Design, Development, Implementation, and Evaluation. The results of the overall validity test data analysis conducted on media expert lecturers obtained a percentage of 70.7%, including the appropriate category. The conclusion of this research is that the development of MeLea Bionic (Media Leaflet Bioentrepreneurship Hydroponics) is appropriate to be used as a reference for making hydroponics to motivate the millennial generation in facing limited land in the city of Semarang.